ANALISIS WACANA KRITIS PROGRAM ACARA KICK ANDY EPISODE PENGAKUAN JOHN KEI DARI BALIK NUSAKAMBANGAN - M. Fauzi; Ismandianto Ismandianto (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2021)
Television is a strategic mass media that can be used to disseminate discourses by various social and political groups that are displayed therein through news and broadcast programs.In 2019 the Talkshow program that has a high rating according to the KPI survey is the Kick Andy program broadcast by Metro TV. It became interesting when Kick Andy invited a murder convict named John Refra alias John Kei as a resource. The research objective was to determine the text structure, social cognition, and social context of John Kei's episode from behind Nusakambangan prison. The method used is descriptive qualitative with Teun Van Dijk's model critical discourse analysis approach. the data was collected by means of observation, interviews and documentation on the episode of John Kei's Confession from Behind Nusakambangan. The results of the research on the text element indicate that the theme is inspired by an inspirational story and things are not known to the wider community about the figure of John Kei. the social cognition, the results show that Kick Andy wants to convey a message to the public not to stigmatize and discriminate former inmates. the social context, this episode was produced by the Directorate General of Corrections, which contained a message calling for John Kei from inside prison to his men and friends to change and repent.